Causes, survival rates, and short-term outcomes of preterm births in a tertiary hospital in a low resource setting: An observational cohort study - Mocking, Martina; Adu-Bonsaffoh, Kwame; Osman, Kwabena A.; Tamma, Evelyn; Ruiz, Alexa M.; van Asperen, Ruth; Oppong, Samuel A.; Kleinhout, Mirjam Y.; Gyamfi-Bannerman, Cynthia; Browne, Joyce L. (Frontiers in Global Women's Health, 2023)
Background Prematurity is the most important cause of death among children under the age of five years. Globally, most preterm births occur in Sub-Saharan Africa. Subsequent prematurity leads to significant neonatal morbidity, mortality and long-term disabilities. This study aimed to determine the causes, survival rates and outcomes of preterm births up to six weeks of corrected age in Ghana. Materials and methods An observational prospective cohort study of infants born preterm was conducted in a tertiary hospital in Accra, Ghana from August 2019 to March 2020. Inclusion was performed within 48 h after birth of surviving infants; multiple pregnancies and stillbirths were excluded. Causes of preterm birth were categorized as spontaneous (including preterm pre-labour rupture of membranes) or provider-initiated (medically indicated birth based on maternal or fetal indications). Survival rates and adverse outcomes were assessed at six weeks of corrected age. Recruitment and follow-up were suspended due to the COVID-19 outbreak. Descriptive statistics and differences between determinants were calculated using Chi-squared tests or Kruskal-Wallis test. Results Of the 758 preterm deliveries, 654 (86.3%) infants were born alive. 179 were enrolled in the cohort and were analyzed. Nine (5%) were extremely preterm [gestational age (GA) < 28 weeks], 40 (22%) very preterm (GA 28–31 weeks), and 130 (73%) moderate to late preterm (GA 32–37 weeks) births. Most deliveries (n = 116, 65%) were provider-initiated, often due to hypertensive disorders in pregnancy (n = 79, 44.1%). Sixty-two infants were followed-up out of which fifty-two survived, presenting a survival rate of 84% (n = 52/62) at six weeks corrected age in this group. Most infants (90%, n = 47/52) experienced complications, predominantly consisted of NICU admission (92%) and interval illnesses (21%) including jaundice and sepsis. Conclusions The incidence of adverse outcomes associated with preterm birth in a tertiary facility with NICU capacity is high. Larger longitudinal studies are needed for an in-depth understanding of the causes and longer-term outcomes of preterm birth, and to identify effective strategies to improve outcomes in resource constrained settings.